The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1136/bmjgh-2016-000041
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based medicine for all: what we can learn from a programme providing free access to an online clinical resource to health workers in resource-limited settings

Abstract: The rapidly changing landscape of medical knowledge and guidelines requires health professionals to have immediate access to current, reliable clinical resources. Access to evidence is instrumental in reducing diagnostic errors and generating better health outcomes. UpToDate, a leading evidence-based clinical resource is used extensively in the USA and other regions of the world and has been linked to lower mortality and length of stay in US hospitals. In 2009, the Global Health Delivery Project collaborated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…This could be particularly beneficial for clinicians caring for a large number of complex patients without access to specialists. We have previously reported on a programme, which provides donated UpToDate subscriptions to clinicians in LMICs, in which we found that most use UpToDate with high frequency, and many report changing their clinical decision making as a result of having access to UpToDate 17…”
Section: Introductionmentioning
confidence: 93%
“…This could be particularly beneficial for clinicians caring for a large number of complex patients without access to specialists. We have previously reported on a programme, which provides donated UpToDate subscriptions to clinicians in LMICs, in which we found that most use UpToDate with high frequency, and many report changing their clinical decision making as a result of having access to UpToDate 17…”
Section: Introductionmentioning
confidence: 93%
“…The potential for their development does exist as there are several associations that could constitute member committees to formulate them and initiate data collation; the Pan‐African Association of Urology, The South African Urology Association, Urological Association of Zambia, and the Egyptian Urological Association all have this capacity. If they developed context‐based, local and regional guidelines, available from a freely available open‐access source [34], an increased uptake of locally relevant data would possibly encourage the provision of a more evidence‐based practice [34, 35].…”
Section: Appropriatenessmentioning
confidence: 99%
“…For users from certain regions (often referred to as "resource-limited settings"), the Up-ToDate database offers topics pertinent to Global Health (https://www.uptodate.com/home/uptodateresource-limited-settings). In addition, various discounts are given to countries in acute need (such as, following a natural disaster) [7]. Furthermore, subscription options may be different between different countries, so it is worth checking the coun-try-specific pricing for subscription (https://www.…”
Section: General Workflow: Electronic Databases On Evidence-based Medmentioning
confidence: 99%